1996
DOI: 10.1097/00006223-199607000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Methodologic Trends in the Healthcare Professions

Abstract: Assessing knowledge and performance on computer is rapidly becoming a common phenomenon in testing and measurement. Computer adaptive testing presents an individualized test format in accordance with the examinee's ability level. The efficiency of the testing process enables a more precise estimate of performance, often with fewer items than traditional paper-and-pencil testing methodologies. Computer simulation testing involves performance-based, or authentic, assessment of the examinee's clinical decision-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…It is claimed that portfolios help to assess and promote critical thinking (Forker & McDonald 1996, Sorrell et al . 1997, Wenzel et al .…”
Section: Advantages and Disadvantages Of Portfoliosmentioning
confidence: 99%
“…It is claimed that portfolios help to assess and promote critical thinking (Forker & McDonald 1996, Sorrell et al . 1997, Wenzel et al .…”
Section: Advantages and Disadvantages Of Portfoliosmentioning
confidence: 99%
“…They are capable of measuring complex intellectual capabilities such as competence. [32][33][34] Since the portfolio is used to capture evidence of individuals' experiences in different forms, as a record to document development, it would be feasible to collect all assessment outcomes as evidence for portfolio building. It is suggested that a portfolio is an effective and efficient way to measure and record students' personal achievements and professional accomplishments in terms of occupational standards and competences.…”
Section: Review Of the Soundness Of Current Assessmentmentioning
confidence: 99%
“…2006), interviews (Girot 1993, Tabari Khomeiran et al. 2006) and portfolios (Forker & McDonald 1996, Girot 2000, McMullan et al. 2003) have been used.…”
Section: Introductionmentioning
confidence: 99%